Successful stopping of biologic therapy for remission in children and young people with juvenile idiopathic arthritis. (15th September 2022) - Kearsley-Fleet, Lianne; Baildam, Eileen; Beresford, Michael W; Douglas, Sharon; Foster, Helen E; Southwood, Taunton R; Hyrich, Kimme L; Ciurtin, Coziana
Abstract: Objectives: Clinicians concerned about long-term safety of biologics in JIA may consider tapering or stopping treatment once remission is achieved despite uncertainty in maintaining drug-free remission. This analysis aims to (i) calculate how many patients with JIA stop biologics for remission, (ii) calculate how many later re-start therapy and after how long, and (iii) identify factors associated with re-starting biologics. Methods: Patients starting biologics between 1 January 2010 and 7 September 2021 in the UK JIA Biologics Register were included. Patients stopping biologics for physician-reported remission, those re-starting biologics and factors associated with re-starting, were identified. Multiple imputation accounted for missing data. Results: Of 1451 patients with median follow-up of 2.7 years (IQR 1.4, 4.0), 269 (19%) stopped biologics for remission after a median of 2.2 years (IQR 1.7, 3.0). Of those with follow-up data ( N = 220), 118 (54%) later re-started therapy after a median of 4.7 months, with 84% re-starting the same biologic. Patients on any-line tocilizumab (prior to stopping) were less likely to re-start biologics ( vs etanercept; odds ratio [OR] 0.3; 95% CI: 0.2, 0.7), while those with a longer disease duration prior to biologics (OR 1.1 per year increase; 95% CI: 1.0, 1.2) or prior uveitis were more likely to re-start biologics (OR 2.5; 95% CI: 1.3, 4.9). Conclusions: This analysis identified factors associated with successful cessation of biologics for remission in JIA as absence of uveitis, prior treatment with tocilizumab and starting biologics earlier in the disease course. Further research is needed to guide clinical recommendations. Graphical Abstract: